IMPLEMENTASI PROGRAM PUSTAKA LATAR BACA DALAM MENINGKATKAN WAWASAN KEISLAMAN DAN MINAT BACA MASYARAKAT - Muhamad Taufiq Ishmat; Acep Mulyadi; Agus Supriyanto (Universitas Islam 45 Bekasi, 2022)
Reading is a habit or culture that is increasingly considered important to be pursued continuously. Reading culture has actually become a concern for the government at both the central and regional levels, although it is not evenly distributed. Several forms of law relating to education and libraries can be evidence of concern. In general, various government policies regarding the growth of a reading culture can be divided into policies for the development of a reading culture through (1) libraries (Library Law) and (2) the development of reading culture through schools (National Education System Law and its derivative regulations). The Law on Libraries regulates the obligations of the central and regional governments in conducting socialization of the Permendiknas on Process Standards, for example, stating that the learning process is designed to develop a love of reading, understanding of various readings, and expression in various trainings or certifications. eroded and almost disappeared. This has an impact that people are easily consumed by hoaxes and are easily provoked just because they read the title of the information without re-examining where the source of the information came from and not reading the whole information. The purpose of this Pustaka Latar Baca program is to increase insight especially in Islamic science and fostering interest in reading in the community in the Auri Jaladhapura Complex area RT: 04 RW:13,the implementation of this Pustaka Latar Baca program is family-based, and the impact of this Pustaka latar baca program is to increase Islamic insight and people's interest in reading..